Livros didáticos de alfabetização PNLD/2010: dimensões do planejamento pedagógico para as propostas de produção de textos escritos - Aline Elvira de Figueredo (2013)
This research is oriented around some basic questions about the organization of educational activities aiming the development of children text writing abilities that have entered a nineyear length elementary school at the age of six. In this work, we have investigated the proposed production of texts in literacy textbooks for the 1st and 2nd years of schooling, distributed by the National Program of Textbooks 2010 (PNLD) for public schools in Brazil in order to analyze the teaching procedures adopted for the development of writing abilities in different text genres during a two-year cycle of literacy. In the constitution of the research corpus, we used, as document source, five out of nineteen teaching literacy collections, approved by PNLD/2010, produced in the context of the implementation of the nine-year length elementary school for students attending the first two years. We had the objective to draw a contrastive profile of these five collections to map the characteristics of their proposal of teaching the written language, considering the following aspects of the production of written texts by the children: mapping the text genres presented to the work of writing during the first years of schooling, the main conditions for the production of written texts that arise in situations of teaching and learning for children in early stage of literacy, the frequency and progression of complexity of the proposed written texts over the first two years of schooling; integration axes of education: reading and text production. The analyzes of these collections have shown us the challenge of teaching to produce texts in the school environment and the teaching of the Portuguese language, in the early years of schooling, should be facing the social function of language. This study has also pointed out that the textbook stands as an important mediator of the sphere of teaching, serving as a tool for both the student and the teacher.